Taxonomia de Aphestia Schiner, 1866 (Diptera: Asilidae: Laphriinae) - Silveira, Alexssandro Emanuel Camargo da (Instituto Nacional de Pesquisas da Amazônia - INPA, 2017)
Aphestia Schiner, 1866 is characterized by the escape about two times the length of the pedicel, post pedicel about 2.5 times the length of escape and pedicel together with truncate apex and also by the presence of lateral marginal macrosetae in all abdominal tergites or restricted to the first two tergites. The genus had three valid species: Aphestia annulipes (Macquart, 1838), Aphestia chalybaea von Röder, 1881 and Aphestia nigra Bigot, 1878. Five synonyms have been already proposed for the Aphestia species and the original descriptions were very succinct, ambiguous and offered few useful characters for the species identification. A taxonomic study of Aphestia was realized with the analisis of external morphological characters as well as male and female terminalia. We analyzed 367 specimens obtained through loan from many national and abroad collections. We found 11 valid species and from these, eight are new: Aphestia amazonica sp. nov.; Aphestia clausicella sp. nov.; Aphestia dicowi sp. nov.; Aphestia fisheri sp. nov.; Aphestia fritzi sp. nov.; Aphestia nigrifemur sp. nov.; Aphestia nigriseta sp. nov. and Aphestia spatulata sp. nov. Two species were redescribed: Aphestia annulipes and Aphestia nigra. Two species that were treated as junior synonym of Aphestia annulipes, had their status revalidated and were redescribed, being: Aphestia brasiliensis Schiner, 1866 sp. reval., e Atomosia affinis Macquart, 1850 sp. reval. Aphestia calceata Schiner, 1867, that was considerated a junior synonym of Aphestia annulipes, is now considered a junior synonym of Aphestia brasiliensis as: Aphestia calceata Schiner, 1867 sin. nov. Atomosia andrenoides Bromley, 1934, that was a junior synonym of Aphestia nigra, was redescribed, had its status revalidated and a new combination with Aphractia Artigas, Papavero & Serra, 1991, was proposed: Aphractia andrenoides (Bromley, 1934) sp. reval.; comb. nov. Aphestia chalybaea von Röder, 1881, was transferred to Cyanonedys Hermann, 1912, becoming Cyanonedys chalybaea (von Röder, 1881) comb. nov. Two new synonyms were proposed for Cyanonedys chalybaea: Cyanonedys leucura Hermann, 1912 sin. nov., type species of the genus, and Clariola nigriscens Ricardo, 1912 sin. nov., that already was a junior synonym of Cyanonedys leucura. The geographic records of the species were increased and a dichotomous illustrated key for the Aphestia species was presented.
Keywords: Atomosiini; moscas ladras; terminália